19 Non-epileptic attacks: establishing the patient population presenting to university hospital southampton. Issue 8 (13th July 2017) - Dichard-Head, Katie; Hunt, Heloise; Smith, Michelle; Crabb, Anthony; Slaght, Sean; Abe, Anne-Mary
Abstract : Objective: To establish the prevalence of non-epileptic attack disorder within a large teaching hospital and compare this population with that in the current literature, Establish proportion of patients with co-morbid epilepsy, Identify prevalence of diagnosed psychiatric co-morbidity in this population group, Review of the management received by this patient cohort. Method: A retrospective study over the time period June 2014 – May 2015, A search was performed on the trust electronic documents using the following keywords: "Non-epileptic attacks"; "NEAD"; "Pseudo seizures"; "Pseudo seizures"; "Dissociative seizures"; "Functional seizures"; "Psychogenic seizures"; "Conversion disorder", NHS numbers of patients with any of the key word diagnoses were collected and electronic records of these patients were reviewed for demographics, diagnoses and management. Results: 162 patients were identified who had a diagnosis of non-epileptic attack disorder. 78% female, 22% male, 50% of female patients and 42% of male patients were diagnosed before the age of 30. The most prevalent age range for women with NEAD was 18–30 years old. There were two most prevalent age ranges for men with NEAD: 18–30 years old and the older age range of 45 years and above. 96% of patients were seen by a neurologist; 42% were seen by a psychiatrist. 22% of patients presented to A and E with non-epileptic attacks. 35% of people with non-epileptic attacks had comorbid epilepsy. 57% of people had a diagnosed psychopathology: 26% had an anxiety-related disorder and 36% had depression. Of the 31 people with NEAD who were in employment, 45% worked in a health care setting, either as a nurse, medical student, health care assistant or in the ambulance service. Conclusion: The demographics in the local area are similar to that described in the literature about non-epileptic attacks. The disorder is more common in women, with a higher proportion of younger women affected. Comorbid psychiatric illness is common, with anxiety and depression the most prevalent diagnoses. In the local population, neurology services saw the majority of patients, with just under half being seen by a psychiatrist. Almost a quarter of patients were seen in the emergency department with non-epileptic attacks. These findings are important in service developments for these patients.